Interferensi Metabisulfit Pada Pengukuran Kadar Sulfur Dioksida (SO2) di Udara Menggunakan Metode Tetrachloromercurat/Parasosanilin - S Sudalma; Sri Sumarni (Jurnal Pengelolaan Laboratorium Pendidikan, 2022)
Sulfur dioxide (SO2) is an irritant gas at concentrations above 250 g/m3 which can cause respiratory problems. Sources of SO2 come from burning fuel containing sulfur. Measurement of SO2 levels in the air using the Tetrachloromercurate (TCM)/Pararosanilin method. PT "B" is a processed wood product company with production using sodium metabisulfite as a mixture for making glue for one type of process product. The purpose of this study was to study the interference of sodium metabisulfite in the measurement of SO2 in the air using the Tetrachloromercurate (TCM)/Pararosanilin method. This research is descriptive observational to explain the phenomena found in monitoring the concentration of SO2 based on SNI 7119-7:2017. The SO2 concentration in the 2017 – 2019 RKL-RPL monitoring results at the glue mixing location was 7-191 g/m3. In the second semester of 2020 measurement, the SO2 concentration was measured at the glue mixing location when the product used sodium metabisulfite as an additive. The activation of SO2 is as follows: activation of the mixer after the process is 646 g/m3, filling the glue mixer is 291 - 314 g/m3, the activity without the use of sodium metabisulfite is 11 - 13 g/m3. The results showed that the concentration of SO2 when the product used a mixture of sodium metabisulfite was higher than the concentration of SO2 when the product did not use sodium metabisulfite. Based on the results and analysis, it can be said that there is an interference of metabisulfite compounds in SO2 measurement due to the absorption of sodium metabisulfite by TCM. This research is helpful for contamination parameters in the workplace  and the threshold determination and reducing the accident and occupational illness caused by exposure to chemicals through controlling and controlling potential hazards.